Hepatitis C Virus in Arab World: A State of Concern. (2nd May 2012) - Daw, Mohamed A.; Dau, Aghnaya A.
Abstract : Hepatitis C virus has been considered to be one of the most important devastating causes of chronic hepatitis, cirrhosis, and hepatic cellular carcinoma. The prevalence of such virus varies greatly over the world. Arab world has a unique geography and consists over nineteen countries who share the same heritage and customs and do speak the same language. In this area, the epidemiology of hepatitis C is not well understandable. Hepatitis C virus was found to be endemic in Arabia. The serostatus of such virus was found to be variable among these countries with uniform patterns of genotypes. Such prevalence varies tremendously according to the risk factors involved. Blood and blood products, haemodialysis, intravenous, and percutaneous drug users, and occupational, habitual, and social behavior were found to be the important factors involved. Hepatitis C will have major social, economic, and even political burdens on such young and dynamic societies. Thus, strategies and clear policy of intervention are urgently needed to combat the consequences of HCV both regionally and at state level of each country.